The protective effects of Ganoderma lucidum polysaccharides on blood physiology, immune function, and organ architecture in growing stressed rabbits. - Alaryani, Fatima S (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: This experiment explored the plausible effects of Ganoderma lucidum polysaccharides (GLP) to reduce the deterioration effects of heat stress (HS) in growing rabbits by studying blood physiology, growth, immunity, inflammation, and organ structure. Materials and Methods: Growing male rabbits (n = 160) were divided into 4 groups and fed a basal diet containing 0 (GLP0), 100 (GLP100), 250 (GLP250), and 400 (GLP400) mg of GLP/kg diet under tropical environmental conditions for 8 weeks. Growth, blood indices, redox state, immune markers, and histology of the liver and kidney were assessed. Results: The addition of GLP (100–400 mg/kg diet) significantly improved the growth indices and reduced the value of the feed conversion ratio (FCR) compared to the GLP0 group (p < 0.05). The liver enzymes, cytochrome C and caspase-3, were significantly decreased by GLP supplementation, while it significantly improved IgG and IgM compared to the control group (p < 0.05). Adding 250 or 400 mg of GLP significantly improved antioxidant enzymes and reduced oxidative stress markers compared to other groups (p < 0.001). Supplementing diets with GLP up to 400 mg/kg diet had lower pro-inflammatory cytokines and greater IL-10 compared to stressed rabbits in the GLP0 group (p < 0.001). The renal and lung tissues were supported by the supplementation of GLP to the stressed rabbit diets. Conclusion: Overall, adding GLP to the diet can be recommended as an effective intervention to alleviate the adverse influences of HS. It enhances growth indices, maintains organ histology, boosts immunity, and reduces pro-inflammatory cytokines and apoptotic biomarkers. J. Adv. Vet. Anim. Res., 12(3): 1059–1069, September 2025 http://doi.org/10.5455/javar.2025.l966